Electronic mechanical braking system executive mechanism design, calculation, and modeling based on dynamic control - Wu, Xinping; He, Rongnian; Ge, Han; Chen, Mengyu (Frontiers in Mechanical Engineering, 2024)
As science and technology develop, automobiles are gradually moving towards intelligence and electrification, which also needs better braking system of automobiles. Therefore, to improve the braking system response speed and braking effect, a longitudinal dynamics control system for automobiles based on the electronic mechanical braking system was proposed, and the electronic mechanical braking system was improved through automatic disturbance rejection control. The experimental results show that the time required for achieving the target clamping force in the electronic mechanical braking system using self disturbance rejection control and proportional integral differential control is only 0.01 seconds, but there is an issue of excessive control in the proportional integral differential system between 0.12 and 0.2 seconds, while the self disturbance rejection controller does not have this problem. Meanwhile, regardless of the interference applied, the electronic mechanical braking system with automatic disturbance rejection control can ensure that the clamping force does not fluctuate. In the joint simulation experiment, the expected acceleration and actual acceleration can remain consistent, and if the expected braking force is 9000 N, then the actual braking force of EMB is also 9000 N. The above results indicate that the vehicle longitudinal dynamics control system using the electronic mechanical braking system not only responses fast, but also has good braking effect, avoiding the problem of excessive control and improving the driving experience.